Indicators of the energy state of the materials that define the performance of the tools. - Буряк, В.Г.; Буряк, А.В. (Problems of Tribology, 2016)
Buryak V.G., Buryak A.V. Indicators of the energy state of the materials that define the performance of the tools.This indicator is the energy state of the materials that define the performance of cutting tools. The attention given to the wear resistance of tools, which enables to increase the processing performance and is an important condition for automated manufacturing.Keywords: Machining, acoustic properties of materials, causal link wear.